Influence of deficit irrigation strategies on fatty acid and tocopherol concentration of almond (Prunus dulcis). (15th April 2015) - Zhu, Ying; Taylor, Cathy; Sommer, Karl; Wilkinson, Kerry; Wirthensohn, Michelle
Highlights: Almond kernel quality was less affected by SDI than RDI. Moderate deficit irrigation (85%) had no detrimental impact on almond lipid. Severe and extreme deficiencies (70% and 55%) decreased almond lipid content. O/L ratio increased by moderate deficiency, but decreased under severe deficiency. Almond tocopherol concentration was not affected by moderate deficit. Abstract: The effects of deficit irrigation on almond fatty acid and tocopherol levels were studied in a field trial. Mature almond trees were subjected to three levels of deficit irrigation (85%, 70% and 55% of potential crop evapotranspiration (ETo ), as well as control (100% ETo ) and over-irrigation (120% ETo ) treatments. Two deficit irrigation strategies were employed: regulated deficit irrigation (RDI) and sustained deficit irrigation (SDI). Moderate deficit irrigation (85% RDI and 85% SDI) had no detrimental impact on almond kernel lipid content, but severe and extreme deficiencies (70% and 55%) influenced lipid content. Unsaturated fatty acid (USFA) and saturated fatty acid (SFA) contents fluctuated under these treatments, the oleic/linoleic ratio increased under moderate water deficiency, but decreased under severe and extreme water deficiency. Almond tocopherols concentration was relatively stable under deficit irrigation. The variation between years indicated climate has an effect on almond fruit development. In conclusion it is feasible to irrigate almond trees using less water than the normal requirement, without significant loss of kernel quality.